Parole de l’imaginaire, imaginaire de la parole dans N’oublie pas de te laver les dents de Philippe Corentin - Isabelle Lebrat (Strenae)
While in the picture book Pipioli la terreur (2006), author Corentin dramatized his story, he dramatizes the act of reception in N'oublie pas de te laver les dents (2009). Reflecting on the border between fiction and reality, the author presents characters who become readers and then authors of their own story. By choosing to tell stories about people’s lives, by playing with points of view and multiplying voices, children's literature can become a wonderful place of experimentation. It is the very fact of the voices themselves, presented in the picture book, their tessitura and vibration, which allows us to listen to an inner experience. In N'oublie pas de te laver les dents, Corentin abandons his storytelling voice for a stereophonic exploration of existence. The author becomes a voice director: he makes us hear the tone that accompanies the word, a certain secret diction, an imperceptible gesture, a slight accentuation, and an oblique meaning.